2021
DOI: 10.3389/fmolb.2021.715764
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Novel Signature and Prediction of the Immune Landscape in Soft Tissue Sarcomas Based on N6-Methylandenosine-Related LncRNAs

Abstract: Background: N6-methylandenosine-related long non-coding RNAs (m6A-related lncRNAs) are critically involved in cancer development. However, the roles and clinical significance of m6A-related lncRNAs in soft tissue sarcomas (STS) are inconclusive, thereby warranting further investigations.Methods: Transcriptome profiling data were extracted from The Cancer Genome Atlas (TCGA) database and Genotype-Tissue Expression (GTEx). Consensus clustering was employed to divide patients into clusters and Kaplan–Meier analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…The correlation between the expression levels of mRNAs and lncRNAs was fully considered. Meanwhile, this method was widely used in the computational genomics field of tumors, such as hepatocellular carcinoma ( Zhou et al, 2021 ), bladder cancer (Ma et al, 2021), soft tissue sarcomas ( Zhang J et al, 2021 ), and breast cancer ( Zhang L et al, 2021 ). There were 601 DELs associated with hypoxia between normal and tumor samples.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between the expression levels of mRNAs and lncRNAs was fully considered. Meanwhile, this method was widely used in the computational genomics field of tumors, such as hepatocellular carcinoma ( Zhou et al, 2021 ), bladder cancer (Ma et al, 2021), soft tissue sarcomas ( Zhang J et al, 2021 ), and breast cancer ( Zhang L et al, 2021 ). There were 601 DELs associated with hypoxia between normal and tumor samples.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study also reveals 13 m6A-related lncRNAs in STS [ 12 ]. The previous study demonstrated that cluster 1 had higher abundance of M0 macrophages and activated dendritic cells and lower abundance of CD8 + T cells [ 22 ]. The authors suggested the positive association of risk score and M0 macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…SARC are characterized by a low incidence rate (approximately 1% of all malignancies in adults and 10–15% of all malignancies in pediatric cancers) but a poor prognosis in most cases ( Hui, 2016 ; Siegel et al, 2019 ). Despite advances in the treatment of STS and osteosarcoma, with comprehensive treatment strategies including surgery, chemotherapy, radiotherapy, and targeted therapy, the survival rate of patients with advanced STSs and BSs needs to be improved ( Zhu et al, 2019a ; Zhang et al, 2021a ; Eaton et al, 2021 ). Although it is difficult to determine the survival for each subtype of sarcoma due to the heterogeneity of the disease, the 5-year survival rates for patients with STS and for patients with bone sarcomas are generally larger than (>) 80% and about 70%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Their analysis indicated that CNVs and mutations of KIAA1429, YTHDF3, and IGF2BP1 were independent risk factors predicting OS and DFS. Zhang et al (2021a ) constructed and validated a signature based on m 6 A-related lncRNAs which could function as independent prognosis-specific predictors in STS, thereby providing novel insights into the roles of m 6 A-related lncRNAs in STS. Noncoding RNAs (ncRNAs), such as long noncoding RNAs (lncRNAs) and microRNAs (miRNAs), function as key regulators of gene expression, and the competitive endogenous RNA (ceRNA) network is a transcriptional regulatory network at the molecular level, consisting of lncRNA, miRNA, and mRNA ( Salmena et al, 2011 ; Zhu et al, 2019b ; Cava et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%